가짜휘발유 판정을 위한 성분 분석 - 임영관(Young-Kwan Lim); 원기요(Ki-Yoe Won); 강병석(Byung-Seok Kang); 박소휘(So-Hwi Park); 정성(Seong Jung); 고영훈(Young-Hoon Go); 김성수(Seong-Soo Kim); 정길형(Gil-Hyoung Jung) (Tribology and Lubricants, 2020)
Petroleum is the most used energy source in Korea with a usage rate of 39.5% among the available 1st energy source. The price of liquid petroleum products in Korea includes a lot of tax such as transportation·environment·energy tax. Thus, illegal production and distribution of liquid petroleum is widespread because of its huge price difference, including its tax-free nature, from that of the normal product. Generally, illegal petroleum product is produced by illegally mixing liquid petroleum with other similar petroleum alternatives. In such case, it is easy to distinguish whether the product is illegal by analyzing its physical properties and typical components. However, if one the components of original petroleum product is added to illegal petroleum, distinguishing between the two petroleum products will be difficult. In this research, we inspect illegally produced gasoline, which is mixed with methyl tertiary butyl ether (MTBE) as an octane booster. This illegal gasoline shows a high octane number and oxygen content. Further, we analyze the different types of green dyes used in illegal gasoline through high performance liquid chromatography (HPLC). We conduct component analyses on the simulated sample obtained from premium gasoline and MTBE. Finally, the illegal gasoline is defined as premium gasoline with 10% MTBE. The findings of this study suggest that illegal petroleum can be identified through an analytic method of components and simulated samples.